A taxonomy of pervasive healthcare systems - CAHILL, VINNY; STOKES, EMMA KATHERINE; MURAS, JOANNA ALICJA (My University, 2006)
Pervasive computing is a developing area. Due to significant technological developments, assistive devices that were impossible to make or that were not even considered for manufacture are now available. The creation of novel smart environments, context-aware assistive devices, and activity monitoring systems have the capacity to provide people with great opportunities to improve their quality of life and increase independence in daily living. These advances in information and communications technology run in parallel to developments in medicine, physiotherapy and psychology. To enable the design of increasingly advanced user-centred systems, dialogue between computer scientists and health care professionals is mandatory. In order to create a framework for dialogue, this paper presents a novel taxonomy of pervasive health care systems. The taxonomy extends the International Classification of Functioning, Disability and Health, which provides standard language and a framework for the description of health and health-related domains. The taxonomy is structured as a hierarchy of the properties of pervasive healthcare systems and can be used as a framework for system classification. It identifies a set of fundamental properties that enable a system to be described according to its user's characteristics, its purpose and environment of use, as well as the technologies employed
Pervasive Health Conference and Workshops, 2006
PUBLISHED
Keywords: taxonomy; International Classification of Functioning, Disability and Health; pervasive computing; health informatics